Estimating the optimal threshold value for foreign investment in Malaysia / Noorzahirah Mohd Sidek and Mahadzir Ismail - Mohd Sidek, Noorzahirah; Ismail, Mahadzir (Research Management Institute (RMI), 2012)
The major thrusts of the 10th Malaysia Plan are geared towards transforming Malaysia into a high income nation. Higher income per capita can only be achieved with higher growth of GDP. In the past, GDP growth in Malaysia is supported by the influx of foreign direct investment which fuels the export-oriented industries. Domestic investment in terms of infrastructure and human capital development further enhance the influx of foreign direct investment into Malaysia. Hence, the main objective of this study is to derived a model which illustrates the dynamic interactions between income per capita, domestic investment and foreign investment. We extend the existing growth model by incorporating the impact of both domestic and foreign investment with a threshold which connotes the novelty of this study. Given the identification of the model, we estimate a threshold value which indicate the minimum or a threshold amount of investment needed to promote income per capita growth. Subsequently, we simulate the impact of shocks of foreign investment and domestic investment on income per capita. Finally, the robustness of the model (s) and the estimation of the threshold value (s) are conducted using heuristic approaches of genetic algorithm, neuro network and support vector machine. The final outcome of this study is the formation of a generic theoretical model which is applicable, at least, in developing countries. The estimated threshold value (s) would be a guide to the government or policy makers as to how much investment is needed to sustain and increase income per capita. Eventually, the theoretical model serves as a benchmark model which would be useful for future simulations, predictions and other extensions in growth modelling in developing world.